The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/tox.22855
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 overexpression protects against cerebral ischemia through Parkin regulation

Abstract: Mitochondrial dynamics and function are important for cell survival regulation under stress. In this study, we report that cerebral ischemia/reperfusion (I/R) injury significantly reduced mitochondrial function through reduced PTEN‐induced kinase 1 (PINK1) expression, ATP (Adenosine triphosphate) levels, and increased oxidative stress compared to sham rats. PINK1 overexpression mice significantly improved mitochondrial function by increased mitochondrial complex I, II, and III activities and ATP levels with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The mechanism(s) involved in mitophagy regulation include PINK1/Parkin-and mitophagy receptors-dependent pathway (Eiyama and Okamoto, 2015). The study showed that PINK1/Parkin acts cooperatively in adjusting mitochondrial balancing function and marking impaired mitochondria (Fan et al, 2019;Wen et al, 2020). Notably, ubiquitylation and deubiquitylation play roles in modulating significantly (Tanaka, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism(s) involved in mitophagy regulation include PINK1/Parkin-and mitophagy receptors-dependent pathway (Eiyama and Okamoto, 2015). The study showed that PINK1/Parkin acts cooperatively in adjusting mitochondrial balancing function and marking impaired mitochondria (Fan et al, 2019;Wen et al, 2020). Notably, ubiquitylation and deubiquitylation play roles in modulating significantly (Tanaka, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…PINK1 and Parkin are two proteins stably expressed in the nervous system of human being [ 39 , 40 ], and crucial for neuronal survival functioning as multipurpose proteins in a variety of toxic insults [ 41 , 42 ]. Notably, PINK1/Parkin pathway has been arisen extensive attention in exploring the interplay between hypoxia-related mitophagy and cerebral ischemia [ 8 , 19 , 22 ]. As a sensor of mitochondrial damage, PINK1 accumulates in the OMM and recruits cytosolic Parkin to damaged mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Then Parkin stimulates the degradation of mitochondria by ubiquitination of mitochondrial proteins [ 43 ]. Cerebral ischemia would alter PINK1 and Parkin expression [ 19 , 22 ]. Demyanenko et al demonstrated that expression of Parkin and PINK1 were increased in the cortical penumbra at 1 h after photothrombotic infarction in Wistar rats [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations